Geolocation of a Known Altitude Target Using TDOA and GROA in the Presence of Receiver Location Uncertainty - Bing Deng; Le Yang; Zheng Bo Sun; Hua Feng Peng (International Journal of Antennas and Propagation)
This paper considers the problem of geolocating a target on the Earth surface using the target signal time difference of arrival (TDOA) and gain ratio of arrival (GROA) measurements when the receiver positions are subject to random errors. The geolocation Cramer-Rao lower bound (CRLB) is derived and the performance improvement due to the use of target altitude information is quantified. An algebraic geolocation solution is developed and its approximate efficiency under small Gaussian noise is established analytically. Its sensitivity to the target altitude error is also studied. Simulations justify the validity of the theoretical developments and illustrate the good performance of the proposed geolocation method.